Analisis Pengaruh Selebritis Spokeperson Terhadap Evaluasi Konsumen pada Iklan IM3 PT Indosat Tbk. - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2009)
The study analyzes the influence of celebrity spokespersons (attractiveness, trustworthiness, and expertise) toward consumer evaluation on the advertisementof IM3 starring by Asmirandah. It takes the public sample of cell phone users who've seen the advertising of IM3 starring by Asmirandah and there are some 100 people arriving in the Kebumen district. The sample techniques that used in this study is non-probability sampling using convenience sampling method. The used Instruments in this study is a questionnaire to obtain needed primary data.The main results of this study shows a significant effect together with celebrity spokespersons (attractiveness, trustworthiness, and expertise) toward the consumer evaluation. The variables of Celebrity spokespersons that have significantly effect to consumers partially toward the consumers evaluation on the advertisement of IM3, starring by Asmirandah is attractiveness and trustworthiness, whereas the expertise variable has no significant effect to consumer evaluation on the advertisement of IM3 starring by asmirandah.